Pertanggungjawaban Pejabat Negara Atas Penyalahgunaan Kewenangan - Rusydi, Yudistira (Jurnal Kepastian Hukum dan Keadilan, 2022)
The Indonesian state has an organizational structure with various functions and a detailed work environment in the overall relationship which is commonly referred to as a position. Besides the enforcement of justice, of course, it cannot be separated from the abuse of authority for state officials. This article is a concept study to analyze the accountability of state officials who commit acts of abuse of authority over their positions from the perspective of state administrative law in Law Number 30 of 2014 concerning Government Administration. The research method used in writing this article is normative juridical with a statutory approach, namely Law Number 34 of 2014 concerning Government Administration. The results of this article reveal that the efforts of state officials to abuse their authority are not in line with their functions based on Law Number 30 of 2014 concerning Government Administration.Keywords: State Officials; Abuse of authority; Accountability